Seroprevalence of anti-SARS-CoV-2 IgG antibodies in HIV-positive and HIV-negative patients in clinical settings in Douala, Cameroon - Sylvie Kwedi Nolna; Sylvie Kwedi Nolna; Miriam Niba; Cedric Djadda; Palmer Masumbe Netongo; Palmer Masumbe Netongo; Palmer Masumbe Netongo (Frontiers in Epidemiology, 2023)
BackgroundThe asymptomatic nature of COVID-19 coupled with differential testing are confounders in the assessment of SARS-CoV-2 incidence among people living with HIV (PLWH). As various comorbidities increase the risk of SARS-CoV-2 infection, it is crucial to assess the potential contribution of HIV to the risk of acquiring COVID-19. Our study aimed to compare the anti-SARS-CoV-2 IgG seroprevalence among people living with and without HIV.MethodsPLWH were enrolled in the HIV units of two health facilities in Douala, Cameroon. Participants were consecutively enrolled, among which 47 were people living with HIV and 31 were HIV-negative patients. SARS-CoV-2 antibody tests were performed on all participants. Overall, medical consultation was conducted. For HIV-positive participants only, viral load, antiretroviral regimen, duration of HIV infection, and duration of antiretroviral treatment were retrieved from medical records.ResultsWe found an overall SARS-CoV-2 IgG seroprevalence of 42.31% within the study population, with a SARS-CoV-2 IgG seroprevalence of 44.6% for PLWH and 38.7% among those without HIV infection; no significant statistical difference was observed. Adjusting for sex, HIV status, and BCG vaccination, the odds of previous SARS-CoV-2 infection were higher among married persons in the study population. Sex, BCG vaccination, and HIV status were not found to be associated with SARS-CoV-2 IgG seropositivity.ConclusionsOur findings support the lack of association between HIV status and susceptibility to SARS-CoV-2 infection. The ARV regimen, suppressed viral load, and Tenofovir boasted ARV regimen might not affect the body’s immune response after exposure to SARS-CoV-2 among PLWH. Thus, if HIV is well treated, the susceptibility to COVID-19 in PLWH would be like that of the general population.